Use of Sawing Waste from Zeolitic Tuffs in the Manufacture of Ceramics - M. Pansini; R. de Gennaro; L. Parlato; M. de'Gennaro; A. Langella; A. Marocco; P. Cappelletti; M. Mercurio (Advances in Materials Science and Engineering)
This paper investigates the thermal transformation of powders of volcanic tuffs that are used as building stones and aims at thermally transforming them into ceramics. The following positive indications concerning this thermal transformation were found: (1) the structural evolution which brings products similar to traditional ceramics, (2) the good ability to give rise to dense and compact final products, and (3) the good mechanical properties and the lovely appearance of the final products. Nevertheless, the high values of linear shrinkages recorded in this work seem to strongly hinder the thermal transformation of this powder-like waste into ceramics. However, mixing this by-product with other powder-like waste exhibiting higher-dimensional stability, such as those deriving from sawing of granites, appears proper.